Implementasi Good Corporate Governance (GCG) dalam Mengukur Risiko dan Kinerja Keuangan Bank Syariah di Indonesia - Yudhistira Ardana (Universitas Muhammadiyah Surabaya, 2019)
Good Corporate Governance (GCG) is one of the key elements in increasing economic efficiency that can help create a conducive and accountable relationship between elements of a company (board of commissioners, board of directors, and shareholders) in order to improve the company's financial performance. This study aims to reveal the influence of Good Corporate Governance (GCG) which is proxied by managerial ownership, institutional ownership, independent board of commissioners and sharia supervisory board in measuring the risk of financing and financial performance of Islamic banks in Indonesia. The results of this study as a whole can be concluded that, Good Corporate Governance (GCG) in measuring risk and financial performance of Islamic banks has no significant effect.